PENDATAAN PENDARATAN IKAN HIU DI PANGKALAN PENDARATAN IKAN (PPI) RIGAIH KABUPATEN ACEH JAYA - Rina Kudadiri; Nurul Najmi; Ilham Fajri (Journal of Aceh Aquatic Sciences, 2022)
Shark is a cartilaginous fish. Sharks can be found in almost all Indonesian waters, both in territorial waters, ocean waters and the Indonesian Exclusive Economic Zone (EEZ). There are various types of sharks found. It was estimated that more than 300 sharks are found in the waters of Aceh Jaya and most of them have the potential to be exploited. The potential for sharks to land in Aceh Jaya is very high, but information about shark catches is still very minimal, therefore a study was obtained from data collection based on shark catches landed at PPI Rigaih to identify species, determine the level of diversity and distribution of sharks, and determine the relationship between length and weight of sharks caught by fishermen at PPI Rigaih, Aceh Jaya Regency as the basis for sustainable shark management. This research was conducted at the Fish Landing Base (PPI) Rigaih, Aceh Jaya Regency. Research activities were carried out starting from August 2 to September 3, 2021.